Room on the broom eaudiobook - Donaldson, Julia (Listening Library, 2020)
This fun family read-aloud i s the perfect way to start Halloween celebrations and an ideal gift book. A sweet story of quick wits, friendship, and inclusivity from the creators of The Gruffalo ! The witch and her cat are happily flying through the sky on a broomstick when the wind picks up and blows away the witch's hat, then her bow, and then her wand!  Luckily, three helpful animals find the missing items, and all they want in return is a ride on the broom.  But is there room on the broom for so many friends?  And when disaster strikes, will they be able to save the witch from a hungry dragon? Julia Donaldson and Axel Scheffler are the creators of many beloved picture books including The Gruffalo , The Gruffalo's Child , The Snail and the Whale , and The Spiffiest Giant in Town . "A surefire read-aloud hit." - School Library Journal